Black Water Rising : A Novel - Locke, Attica (New York : Harper Perennial, 2010)
When African-American lawyer Jay Porter jumps into the bayou to save a drowning white woman in Houston, Texas, in 1981, he finds his practice and life in danger when he becomes embroiled in a murder investigation involving Houston's elite.
Keywords: African American lawyers -- Fiction; Petroleum industry and trade -- Fiction; Corporations -- Fiction -- Corrupt practices; Legal stories; Suspense fiction